Prospective Associations of Maternal Dietary Patterns and Postpartum Mental Health in a Multi-Ethnic Asian Cohort: The Growing up in Singapore towards Healthy Outcomes (GUSTO) Study - Teo, Cherlyen (Nutrients, 2018)
Diet in the first month postpartum, otherwise known as “the confinement diet” in Asia, has unique characteristics that are influenced by traditions, cultures, and beliefs. We aimed to characterize dietary patterns during confinement period in a multi-ethnic Asian cohort and examined their associations with postpartum depression (PPD) and anxiety (PPA). Dietary intakes of 490 women were ascertained in the first month postpartum using 3-day food diaries and dietary patterns were derived by factor analysis. Participants completed the Edinburgh Postnatal Depression Scale (EPDS) and State-Trait Anxiety Inventory (STAI) at three months’ postpartum; higher scores are indicative of more depressive and anxiety symptoms, respectively. Four dietary patterns were identified: Traditional-Chinese-Confinement diet, Traditional-Indian-Confinement diet, Eat-Out diet and Soup-Vegetables-Fruits diet. The Traditional-Indian-Confinement diet was associated with less PPD symptoms [β (95% CI) −0.62 (−1.16, −0.09) EPDS score per SD increase in diet score] and a non-significant trend with reduced probable PPD (EPDS scores ≥ 13) [OR (95% CI) 0.56 (0.31, 1.01)]. The Soup-Vegetables-Fruits diet was associated with less PPA symptoms [β (95% CI) −1.49 (−2.56, −0.42) STAI-state score]. No associations were observed for other dietary patterns. Independent of ethnicity, adherence to the Traditional-Indian-Confinement diet that is characterized by intake of herbs and legumes, and Soup-Vegetables-Fruits diet high in fruits, vegetables and fish during the postpartum period were associated with less PPD and PPA symptoms, respectively.